KRITIK SOSIAL DALAM CERITA PENDEK BERJUDUL “KEMARAU” KARYA ANDREA HIRATA - Nuurii, Luthfi; Septiani, Weni (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This article discusses social criticism in the short story titled "Kemarau" by Andrea Hirata. The discussion of this article will focus on qualitative research, with descriptions of things or events in short stories relating to social criticism. From the results of the research, three social criticisms in the short story of "Kemarau" are: (1) criticism of political problems, when people feel disappointed with government promises that are not implemented (2) criticism of the economy, where the people in the village can not feel the progress and progress of infrastructure such as people in big cities and (3) criticism of cultural preservation. The cause of such social criticism can be influenced by the negligence factor of the government when it has occupied its position. The government seems to forget the promises that have been pronounced in the period before occupying the seat of office. From the short story it can be seen that literary works not only display a positive impression or message but can contain implicit things, such as criticizing or sarcastic.